Significance of Borrelia infection in development of dilated cardiomypathy (a pilot study) - Bartůnĕk, P; Gorican, K; Veiser, T; Táborský, M; Hulínská, D (Prague medical report, 2007)
A heart involvement known as Lyme carditis (LC), a consequence of Lyme borreliosis (LB), is relatively rare in contrast to the involvement of skin, joints and nervous system; it accounts for < 4% of all these patients in European countries. However, the diagnosis of the disease belongs to the most difficult challenges. While various forms of AV blocks dominate in the USA as confirmed by the literature, there is a clear predominance of arrhythmias of various incidence in the Czech Republic. The authors of this article focused on the form belonging to the rarest manifestations of LC, namely dilated cardiomyopathy (DCMP). The goal was to elucidate the etiological participation of Borrelia infection in the development of DCMP, which has attracted controversial opinions so far. In total, 33 patients with DCMP were enrolled in the study, 23 males and 10 females, with mean age 57.7 years (range 24-76 years). ELISA NRLB KC 90 method was used in all blood samples for detection of Borrelia infection (BI), Western blot method was used for confirmation, followed by identification of DNA of pathogenic Borreliae using PCR method. Bioptic material was examined by electronmicroscopy with an attempt to detect Spirochaetae in myocardium. 16 patients were excluded from the study owing to the absence of signs of LB. The study group included 17 patients (3 females, 13 males) with mean age 58 years (range 43-76 years), in whom the presence of Bb was proved by identification of DNA of pathogenic Borreliae or by electronmicroscopic detection of Spirochetae in myocardial bioptic sample. The findings obtained during the study confirmed that BI very probably participated in the development of dilated cardiomyopathy. It may be concluded that most of cases were either unapparent forms of LB or insufficiently treated cutaneous forms of this disease.
Keywords: DNA bakterií; Humans; Borrelia; lidé středního věku; Lyme Disease; lymeská nemoc; Female; Aged; dospělí; senioři; lidé; Cardiomyopathy, Dilated; Adult; DNA, Bacterial; ženské pohlaví; Male; Middle Aged; mužské pohlaví; dilatační kardiomyopatie